On Word-Building Families - Закарьян, М. (Kalbotyra, 1977)
The paper deals with the problems of word-building in the Old Byelorussian language in the period of the 16th—mid-17th centuries. The investigation is carried on in terms of word-building which are treated as subsystems within the general derivation system of the language. In the paper there are given arguments for such a conception of the word-building family and advantages of this method over the other methods of investigation of the derivation system of the language.